Challenges of earth pressure balance tunnelling in weathered granite with boulders. Issue 6 (11th December 2020) - Zhang, Nan; Shen, Shui-Long; Zhou, An-Nan; Lyu, Hai-Min
Abstract : This paper presents a case history of an earth pressure balance shield tunnelling project in Guangzhou, China. It beings with an explanation of the project background and geological conditions on site. The shield machine passed through variably weathered granite with randomly distributed boulders. Based on the different geological formations, the tunnel alignment was classified into eight different zones. Tunnel face instability, ground collapse, groundwater ingress and excessive cutter wear were identified to be critical factors that affected the performance of the tunnel boring machine (TBM) and delayed the construction schedule. The impact mechanism on the surroundings during tunnelling was analysed. Countermeasures are recommended to improve the performance of TBMs in such difficult ground conditions on future projects.